Primary Pituitary Lymphoma in Immunocompetent Patients: A Report on Two Case Studies and the Review of Literature - Duan, Lian; Liu, Jie; Zhang, Yan; Cui, Lijia; Zhai, Xiao; Pan, Boju; Lu, Lin; Pan, Hui; Yao, Yong; Zhu, Huijuan (Frontiers in Endocrinology, 2021)
Primary pituitary lymphoma (PPL) represents an extremely rare entity. Here, we have reported two recently identified cases of immunocompetent PPL having diffuse large B- cell lymphoma by surgical biopsy. Both patients had hypopituitarism, with one patient developing right ptosis. In both patients, MRI and FDG-PET/CT depicted sellar mass that extended into the cavernous sinus with the right sphenoid also present in one of the patients. No systemic disease was found in these two patients. Surprisingly, we found that both patients had infiltrative lesions in sphenoid sinus mucosa pathologically, but the sphenoid bones that composed the sellar base were visually intact during the biopsy procedure. Chemotherapy was administered to both patients, where one patient achieved remission at the recent follow-up, whereas the other one did not respond to the treatment. The diagnosis of PPL is usually difficult if solely dependent on history, clinical presentation, biochemical indexes, and radiographic findings. We have also updated and reviewed the epidemiologic features, clinical presentations, pathological characteristics, potential mechanisms, therapeutic orientation, and prognostic advances of PPL. A total of 40 cases (including ours and four pediatric patients), histologically diagnosed, were analyzed in terms of clinical presentation, endocrine abnormality, radiological features, pathology, treatment, and follow-up. Hypopituitarism and headache were the most common presentation of PPL, while diabetes insipidus was reported in 13 patients (43.3%). B cell lymphoma was the most common type of pathology, followed by T-cell and NK/T cell. PPL was more invasive in nature at the suprasellar region (72.5%), cavernous sinus (52.5%), and sphenoidal sinus (27.5%) in 29, 21, and 11 patients, respectively. Pediatric patients with PPL seem to be different compared to their adult counterparts in terms of pathogenesis, clinical presentation, and radiological features. The management of PPL usually follows the treatment protocols for PCNSL but has a poor prognosis compared to the pituitary involvement of systemic lymphoma.